Quantum phase diagram of a frustrated antiferromagnet on the bilayer honeycomb lattice - Zhang, Hao (2016)
We study the spin-1/2 Heisenberg antiferromagnet on a bilayer honeycomb lattice including interlayer frustration. Using a set of complementary approaches, namely, Schwinger bosons, dimer series expansion, bond operators, and exact diagonalization, we map out the quantum phase diagram. Analyzing ground-state energies and elementary excitation spectra, we find four distinct phases, corresponding to three collinear magnetic long-range ordered states, and one quantum disordered interlayer dimer phase. We detail that the latter phase is adiabatically connected to an exact singlet product ground state of the bilayer, which exists along a line of maximum interlayer frustration. The order within the remaining three phases will be clarified.